Encountering Suffering at Work in Health Religious Organizations: A Partial Least Squares Path Modeling Case-Study - Sánchez-Hernández, Maria Isabel; Gismera-Tierno, Eduardo; Labrador-Fernández, Jesus; Fernández-Fernández, José Luis (Frontiers in Psychology, 2020)
Health religious organizations tend to offer individual attention to patients in line with their spiritual character and, at the same time, the highest service quality. This study puts the attention on the nurse-patient relationship and empirically explores a theoretical model that links nurses´ suffering at work with personal´s willingness to engage in a therapeutic and spiritual relationship with patients and the consequent effect on quality. Data has been collected in the city of Madrid (Spain) in the month of June 2019 in Santa Elena Clinic. An analytical case-study based on Partial Least Squares path modeling is the chosen method to verify the cause-effect hypothesized relationships. This study contributes to the current academic literature by providing new knowledge and empirical evidence on the topic of the future of work in health religious organizations. The main conclusion is the necessary inclusion of suffering, even in good places to work, as a key indicator for a better management. Results should be a useful source of information for practitioners that seek to implement better human management systems in these organizations.